Dalit Interpretations of the Purāṇas: Subaltern Hermeneutics and the Reclamation of Textual Authority - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This paper examines emerging Dalit interpretations of Purāṇic literature, analyzing how marginalized communities are developing distinctive hermeneutical approaches to traditional Hindu texts. Through interviews with Dalit scholars, analysis of contemporary Dalit religious literature, and ethnographic research in Dalit religious communities, this research documents how subaltern readings of the Purāṇas challenge dominant Brahmanical interpretations while simultaneously reclaiming these texts as part of a shared cultural heritage. The study reveals sophisticated interpretive strategies that center previously marginalized characters, highlight themes of social justice within the texts, and recontextualize narratives to address contemporary experiences of discrimination. By approaching the Purāṇas from positions of marginality, Dalit interpreters reveal dimensions of these texts that have been obscured by dominant hermeneutical traditions, contributing new perspectives to Hindu textual studies. This research contributes to both Dalit studies and religious hermeneutics by illuminating how textual reinterpretation serves as a form of resistance and empowerment for historically excluded communities within Hindu traditions.